Equity & trusts - Dixon, Martin (Cavendish Q & A series, 1995)
This work is part of the Questions and Answers series, designed specifically for the examination candidate. The books are written by experienced law lecturers, who are themselves examiners. Each book in the series contains 50 questions and suggested answers covering the range of examination topics commonly found in law degrees, CPE and vocational examinations at many universities and colleges. The purpose of the books is to illustrate the clear logical approach which is expected of a good honours degree student. Each book is divided into chapters according to topic area and each chapter begins with an introduction outlining the main points which should have been mastered before tackling the questions in that chapter. Each answer is supplemented by additional notes which pick up points of particular difficulty or refer to additional or alternative material which could be used in the answer. This text in the Questions and Answers series aims to help students penetrate some of the mysteries of equity and trusts by providing practical answers to typical examination questions. At the same time, the author also presents the subject as a whole, so that teachers may also use it.